OPTIMIZING THE PLACEMENT OF A WORK-PIECE AT A MULTI-POSITION ROTARY TABLE OF TRANSFER MACHINE WITH VERTICAL MULTI-SPINDLE HEAD - N. N. Guschinski; V. E. Zdanovich; B. M. Rozin (Informatika)
The problem of minimizing the weight of transfer machine with a multi-position rotary table by placing of a work-piece at the table for processing of homogeneous batch of work-pieces is considered. To solve this problem the mathematical model and heuristic particle swarm optimization algorithm are proposed. The results of numerical experiments for two real problems of this type are given. The experiments revealed that the particle swarm optimization algorithm is more effective for the solution of the problem compared to the methods of random search and LP-search.